2023
DOI: 10.1155/2023/6551544
|View full text |Cite
|
Sign up to set email alerts
|

VEXAS Syndrome in a Patient with Myeloproliferative Neoplasia

Abstract: VEXAS syndrome stands for vacuoles, E1 enzyme, X-linked, autoinflammatory, somatic syndrome. The syndrome is a combined hematological and rheumatological condition caused by a somatic mutation in the UBA1. There is an association between VEXAS and hematological conditions such as myelodysplastic syndrome (MDS), monoclonal gammopathies of uncertain conditions (MGUS), multiple myeloma (MM), and monoclonal B-cell lymphoproliferative conditions. There are not many descriptions of patients having VEXAS in combinati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…One case reported stabilization of VEXAS clinical course with a combination of prednisolone, anagrelide and ruxolitinib. The patient experienced partial remission, fewer hospitalizations and more stabilized haemoglobin and thrombocytes 38 . Loschi et al.…”
Section: Vexas Syndrome Treatmentsmentioning
confidence: 89%
See 2 more Smart Citations
“…One case reported stabilization of VEXAS clinical course with a combination of prednisolone, anagrelide and ruxolitinib. The patient experienced partial remission, fewer hospitalizations and more stabilized haemoglobin and thrombocytes 38 . Loschi et al.…”
Section: Vexas Syndrome Treatmentsmentioning
confidence: 89%
“…The patient experienced partial remission, fewer hospitalizations and more stabilized haemoglobin and thrombocytes. 38 Loschi et al reported a 60-year-old male with VEXAS with worsening inflammation flares with ruxolitinib tapering prior to allogeneic stem cell transplantation. Eighty-one days posttransplantation, the patient was able to taper corticosteroids and ruxolitinib.…”
Section: Role Of Biologic Agentsmentioning
confidence: 99%
See 1 more Smart Citation
“…Limited but promising results have been achieved with the JAK1/2 inhibitor ruxolitinib or the hypomethylating agent 5-azacytidine [8][9][10]18,24]. Due to this fact and the absence of evidence-based recommendations, we treated our patients with these two substances.…”
Section: Discussionmentioning
confidence: 99%
“…Common clinical features observed in VEXAS syndrome patients include skin lesions (83%), non-infectious fever (64%), weight loss (62%), lung involvement (50%), ocular symptoms (39%), relapsing chondritis (36%), venous thrombosis (35%), lymphadenopathy (34%), and arthralgia (27%) [3]. Additionally, patients with VEXAS syndrome experience progressive hematologic abnormalities such as macrocytic anemia, thrombocytopenia, and myeloid dyspoiesis [8][9][10]. In a substantial number of cases, the disease may progress to an overt hematologic malignant condition [11][12][13].…”
Section: Introductionmentioning
confidence: 99%